Obtaining infecting larvated eggs of toxocara canis for inoculation of balb/c mice in experimental studies (Gaceta de Ciencias Veterinarias, 2022)
Infection with Toxocara canis (T. canis) represents an important parasitic zoonosis with worldwide distribution. Man becomes infected by involuntarily ingesting larvated eggs of the parasite. It is important to know the behavior of T. canis in different human organs, by carrying out experimental studies in mice of the BALB/c strain, for which it is necessary to infect them with viable larvated eggs of the parasite. The objective of this research was to obtain infective larvae eggs of Toxocara canis for inoculation of BALB/c mice in experimental studies. We worked with 12 adult females of T. canis, from a mixed-breed female dog (Lupus canis familiaris) puppy, with clinical signs of parasitosis and a positive coprological result for Toxocara spp., which was treated with pyrantel pamoate at a single dose of 15 mg/kg. orally. The uterus was dissected from these females and a total of 1.200.000 eggs of the parasite were obtained, which were incubated in 2.5% formalin/ringer's solution at a temperature of 25 °C and a humidity of 98% for 4 weeks, they were oxygenated and monitored every 3 days, observing the different phases of their development. From the first to the last review, a viability of 99 to 99.5% was found, that is, only 0.5 to 1% of the total eggs did not develop the larval form. The infective larvae eggs of T. canis represent the most important risk factor in the transmission of this disease.